Insureds’ Perception towards Insurance Services in Pokhara - Gurung, Jas Bahadur (REPOSITIONING The Journal of Business and Hospitality, 2016)
The basic objective of this study is to analyze the perception or opinion of Insured on the services provided by the insurers, agents and surveyors in Pokhara valley. Study shows 71.57 percent respondents agreed insurance creates awareness among people. Similarly, 73.53 percent respondents agreed it also provides social security. Regarding interest rates on loan, 57.43 percent respondents are indifferent on their opinion that whether the rate of interest on loan is cheaper or not but 30.69 percent are agreed that interest on loan is cheaper. Sixty-six point six seven percent respondents are neutral that payment of loan installment is easier or not but 22.22 percent opined installment payment is easier in insurance companies. In the context of satisfactoriness of insurance services, 50.49 percent respondents agreed that services of insurance companies are satisfactory. Out of 92 respondents, 71.74 percent argued that they are satisfied with the services of insurance agents and 28.26 percent are not satisfied. Of the total respondents, 35.89 percent agreed on the performance of insurance surveyors is satisfactory and free of bias. But 33.33 percent respondents on the other are neutral about the performance and behavior of surveyors. On the whole, the above facts imply that the perception of insureds towards insurance services is satisfactory in Pokhara valley. Repositioning Vol.1(1) 2016: 23-36